2009
DOI: 10.1111/j.1472-765x.2009.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

ERIC-PCR-based strain-specific detection of phenol-degrading bacteria in activated sludge of wastewater treatment systems

Abstract: Aims:  To evaluate the use of Enterobacterial Repetitive Intergenic Consensus PCR (ERIC‐PCR)‐derived probes and primers to specifically detect bacterial strains in an activated sludge microbial community. Methods and Results:  ERIC‐PCR was performed on two phenol‐degrading bacterial strains, Arthrobacter nicotianae P1‐7 and Klebsiella sp. P8‐14. Their amplicons were DIG labelled for use as probes and then hybridized with ERIC‐PCR fingerprints. The results showed the distinct band patterns for both bacterial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Wang et al . () and Yuan et al . () reported the bioremediation of aromatic hydrocarbons, such as phenol, phenanthrene and pyrene under high enantiomeric excess with A. nicotianae .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Wang et al . () and Yuan et al . () reported the bioremediation of aromatic hydrocarbons, such as phenol, phenanthrene and pyrene under high enantiomeric excess with A. nicotianae .…”
Section: Resultsmentioning
confidence: 89%
“…The previous studies on A. nicotianae mainly focused on effect of metal ions, such as copper (Nakajima 2002), uranyl ion (Takehiko 2002), lithium (Takehiko 2005), and cadmium (Tsuruta et al 2014). Wang et al (2009) and Yuan et al (2009) reported the bioremediation of aromatic hydrocarbons, such as phenol, phenanthrene and pyrene under high enantiomeric excess with A. nicotianae. However, this study is the first to report that A. nicotianae degrades organochlorine pesticides.…”
Section: Biodegradation Of Other Organochlorine Pesticides By Strain mentioning
confidence: 99%
“…The genetic diversity of Paenibacillus populations in the rhizosphere of wheat has been reported by using ERIC-PCR and the fingerprints were highly reproducible (Guemouri-Athmani et al, 2000). The use of ERIC-PCR for rapid and reliable detection of Arthrobacter has been reported (Wang et al, 2009). RAPD-PCR has been successfully used for genetic fingerprinting and molecular typing for many microorganisms (Gurtler et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A number of useful polymorphic techniques, such as RAPD, repetitive-sequence-based PCR (rep-PCR), enterobacterial repetitive intergenic consensus PCR (ERIC-PCR), and amplified fragment length polymorphism (AFLP), have been used for the detection of organism-specific distinctive DNA sequences. [28][29][30][31][32][33][34] Although only a few reports describe specific genetic detection methods applicable at the strain level, Fujimoto et al, 35) Maruo et al, 36) and Tilsala-Timisjärvi & Alatossava 37) reported the use of RAPD for strain-specific detection of Lactococcus lactis ssp. cremoris FC, Lactobacillus casei Shirota, and Lactobacillus rhamnosus Lc 1/3, respectively.…”
Section: )mentioning
confidence: 99%